Changes of micro elements, activity of metalloenzymes-antioxidants and metal-dependent enzymes in the blood serum of patients with periodontitis influenced by complex non-surgical treatment - Halyna Melnychuk; Veronika Kateryniuk; Hanna Semeniuk; Nataliia Shovkova; Roksolana Kashivska (Pensoft Publishers, 2023)
Data provided by WHO show that the prevalence of aggressive periodontitis is observed in almost 19% of the adult world population and is associated with the destruction of the attachment apparatus and premature tooth loss. Development of a periodontal pocket and foci of infection also negatively affect the body on the whole. Despite the great number of the researches in this field and the dramatic improvement in the treatment and prophylaxis, the problem of high prevalence of periodontal diseases remains actual. The article demonstrates the biochemical changes of Iron, Copper, Zinc, Manganese and metal-dependent oxidant-antioxidant enzymes in the blood serum of patients diagnosed with periodontitis gained after complex periodontal therapy with Spirulina platensis of blue-green microalgae. It was established that the micro- and macro-elements in the introduced agent significantly contribute to the correction of the Iron, Copper, Zinc and Manganese content, they also influence the activity of metaloproteins therefore, normalize the antioxidant defense of the body in general.